A Felvidék történeti régiói - Csüllög, Gábor (Közép-Európai Közlemények, 2011)
Upper Hungary has been a region of great significance in Hungarian history. It simultaneously comprises a large geographical, cultural, linguistic, ethnic and ethnographic area. It is difficult to provide an exact definition for it or its borders since they depend on the particular historical era and field of science scrutinizing them. On the basis of both regionalism as well as the examination of the historical process of regionalization, it can be stated that this region has never been a uniform one since, in various historical periods, it has been divided into regional units of various character defined by connections in its spatial structure, Regionalization has never organized it into a separate region as it has Transylvania. Instead, several regions were formed from spatial connections during the past centuries. Moreover, in certain periods of history, the state itself formed a number of political regions as well. By the end of the 19the century, Upper Hungary had lost some of its earlier historical and spatial-structural character and, therefore, has been generally defined on the basis of its regional as well as complex ethnic characteristics.